Revisiting Purchasing Power Parity for Central Asian Countries Using Threshold Cointegration Tests - Lau, Evan; Liew, Venus Khim-Sen; Puah, Chin Hong; Choong, Chee-Keong (AccessEcon, 2010)
This study finds evidence supportive of the Purchasing Power Parity for Azerbaijan and Kazakhstan using threshold cointegration tests. This finding suggests the existence of an asymmetry relationship between exchange rate and relative prices. The asymmetric relationship may be due to the heavily regulated price and exchange rate systems in these transition economies for the benefits of trade competiveness.